2016
DOI: 10.1177/0960327116650009
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Benzo[a]pyrene-induced oxidative stress and pulmonary toxicity by Naringenin in Wistar rats: A plausible role of COX-2 and NF-κB

Abstract: Naringenin is a naturally occurring flavanones and has been found to exhibit free radical scavenging, enzyme inhibition, antioxidants, anti-inflammatory, and anticancer activities. Present study was designed to evaluate the protective role of naringenin against benzo[a]pyrene (B[a]P)-induced oxidative stress and pulmonary toxicity. Rats were treated with naringenin at a dose of 100 mg/kg body weight (b. wt.), by oral gavage. B[a]P in a single dose of 50 mg/kg b. wt. was given intraperitoneally. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Naringenin has shown the ability of combating LP in many organs, tissues and cells, for example, in lung[ 45 ], ankle joints (arthritis model)[ 46 ], retina of streptozotocin-induced diabetic rats[ 47 ], SH-SY5Y cells[ 48 ], cardiomyoblast cells[ 49 ], skin[ 50 ], testis[ 51 ] and, interestingly, in liver[ 44 , 52 , 53 ]. It can be concluded that, in contrast to the results obtained in chemical antioxidant assays, the beneficial effects of naringenin against LP in systems involving living organisms or cells, the flavanone shows strong activity.…”
Section: Antioxidant Effects Of Naringenin Beyond the Structure Actimentioning
confidence: 99%
“…Naringenin has shown the ability of combating LP in many organs, tissues and cells, for example, in lung[ 45 ], ankle joints (arthritis model)[ 46 ], retina of streptozotocin-induced diabetic rats[ 47 ], SH-SY5Y cells[ 48 ], cardiomyoblast cells[ 49 ], skin[ 50 ], testis[ 51 ] and, interestingly, in liver[ 44 , 52 , 53 ]. It can be concluded that, in contrast to the results obtained in chemical antioxidant assays, the beneficial effects of naringenin against LP in systems involving living organisms or cells, the flavanone shows strong activity.…”
Section: Antioxidant Effects Of Naringenin Beyond the Structure Actimentioning
confidence: 99%
“…Diosmin treatment seems to have a positive effect in improving cardiac function and subdue oxidative stress in the heart . Various other flavonoids, namely naringenin, and catechin, are known to ameliorate oxidative stress and inflammation in animals treated with B(a)P. However, no reports are available for the protective role of Diosmin in lung injury induced by various environmental contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al found that NRG pretreatment inhibits neuroapoptosis and ameliorates cognitive impairment in rats exposed to isoflurane anesthesia by regulating the PI3/Akt/PTEN signaling pathway and suppressing NF- κ B-mediated inflammation [ 11 ]. NRG also inhibits stress-induced autophagy [ 12 ] and has a protective effect on oxidative stress-induced lung damage [ 13 ]. This suggests that NRG can inhibit MP-induced inflammatory responses and pulmonary fibrosis by suppressed autophagy.…”
Section: Introductionmentioning
confidence: 99%